Avoidance and subversion of eukaryotic homeostatic autophagy mechanisms by bacterial pathogens - Miller, Cheryl (J Mol Biol, 2016)
Autophagy is a lysosomal recycling process conserved in eukaryotes, which maintains cellular homeostasis during stress and starvation conditions by degrading and recycling proteins, lipids and carbohydrates, ultimately increasing nutrient availability. An additional function of autophagy, termed xenophagy, is to detect, capture and destroy invading microorganisms, such as viruses, bacteria and protozoa, providing autophagy with a role in innate immunity. Many intracellular pathogens have however developed mechanisms to avoid xenophagy, and have evolved strategies to take advantage of select autophagic processes to undergo their intracellular lifecycle. This review article will discuss the molecular mechanisms used by the intracellular bacterial pathogens Francisella spp. and Brucella spp. to manipulate components of the autophagic pathway, promoting cytosolic growth in the case of Francisella spp., and facilitating cellular egress and cell-to-cell spread in the case of Brucella spp. These examples highlight how successful, highly infectious bacterial pathogens avoid or subvert host autophagy mechanisms normally employed to maintain eukaryotic homeostasis.